Ayurvedic Management of Psoriasis - Keerthy S L; Seemaja G; E Anusankar (International Journal of Ayurveda and Pharma Research, 2025)
Psoriasis is a common chronic, immune-mediated dermatological condition characterized by the rapid proliferation of keratinocytes, leading to the formation of erythematous thick, scaly indurated plaques. It is affecting approximately 2-3% of the global population, it possesses significant physical and psychological burdens. The aetiology of psoriasis is multifactorial, involving genetic predisposition, environmental triggers, behavioural changes and immune system dysregulation. This disease commonly manifests on the skin over elbows, knees, scalp, chest, lumbo-sacral areas, and intergluteal clefts. At present, there is no permanent cure, and modern medical science focuses on providing symptomatic relief. However, skin disorders often respond better to Ayurvedic treatment. A 37-year-old male, presented to the OPD with complaints of itching all over his body, along with thickened silvery scaling, especially over the scalp, with an erythematous base and red patches all over his body for 10 years. He was exhausted and depressed after finding no relief on trying various systems of medicine. After examination of the patient, an Ayurvedic treatment protocol was designed, including external and internal medication. Significant improvement was noticed in all symptoms. Assessment was done using PASI score which reduced from 24.8 to 6. The duration of treatment was 45 days, follow-up after a month.